2021
DOI: 10.3390/ijerph18199971
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of SARS-CoV-2 Anti-Spike IgG Antibody in Women and Children in Madinah, Saudi Arabia: A Single-Center Study

Abstract: Background: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Information on the prevalence of SARS-CoV-2 antibodies in women and children in Madinah has been limited. The current study aimed to evaluate SARS-CoV-2 IgG seropositivity among women and children at Madinah Maternity and Children’s Hospital. Methods: In this cross-sectional study, 579 participants were recruited between January and April 2021 from Madinah Maternity and Children’s Hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…Our figure is presumed to be inflated with COVID-19 infection cases that happened prior to pregnancy or during lactation. A report from Madinah in Saudi Arabia found that 50.2% of pregnant women were seropositive for COVID-19 [ 24 ].…”
Section: Discussion Of the Key Findingsmentioning
confidence: 99%
“…Our figure is presumed to be inflated with COVID-19 infection cases that happened prior to pregnancy or during lactation. A report from Madinah in Saudi Arabia found that 50.2% of pregnant women were seropositive for COVID-19 [ 24 ].…”
Section: Discussion Of the Key Findingsmentioning
confidence: 99%
“…In this retrospective study, data and serum samples from 283 healthy individuals collected for previous projects [ 16 , 17 ] were used. Male participants (n = 144) were blood donors at the central blood bank in Medina province.…”
Section: Methodsmentioning
confidence: 99%
“…Signi cantly higher anti-S IgG levels were observed in children than in women. Compared with women, children had higher odds of high SARS-CoV-2 anti-S IgG levels (7). Most studies about the level of IgG antibody in COVID-19 patients were related to plasma donations for treatment of COVID-19 patients(8, 9), and screening seroprevalence of anti-SARS-CoV-2 antibodies in the population during the epidemic.…”
Section: Introductionmentioning
confidence: 99%